Keperluan Media Wordwall pada Materi Sifat Allah Dikelas VII MTs Terpadu Berkah Palangka Raya - Pastilah, Lijar; Pratama Putra, Aulia (Muróbbî: Jurnal Ilmu Pendidikan, 2024)
The aim of this research is to find out how effective the use of Wordwall-based learning media is in teaching material about the nature of God in class VII MTS Terpadu Berkah Palangka Raya. This research also aims to understand how this media can help students understand the concept of divinity and religious values, with a focus on increasing student interest in learning and engagement. This study uses mixed methods with an explanatory design. To find out how important Wordwall media is in the learning process, 33 students and teachers were interviewed to collect data. Data analysis was carried out by calculating the percentage of scores given by students on the questionnaire. The research results showed that 82% of students felt they needed Wordwall-based learning media, and the use of this media increased student interaction and participation. Students indicated that this medium made the learning process more interesting and helped them understand the topic better. Thus, the use of Wordwall also helps students build character and morality, which is the main goal of Islamic religious education. This research found that Wordwall-based learning media was effective in increasing students' understanding of the nature of God and religious values. Therefore, teachers must continue to learn to use innovative learning media to make learning more fun and meaningful.